Analisis Tutur Dan Tindak Tutur Dalam Media Sosial: Studi Kasus Sea-Blings Vs Knetz - Adinda Andini; Delfira Almuharomah Lubis; Ledy Novwanty Nainggolan; Shema Eklesiya Hutasoit; Wijar Pakpahan; Herning Puspitarini; Oky Fardian Gafari (CV. SINAR HOWUHOWU, 2026)
Social media has become a space for interaction that allows users to express themselves quickly and openly. This often gives rise to debate, especially when involving communities with different cultural backgrounds, such as the Sea-Blings and Knetz. This study aims to analyze the forms of speech and speech acts that emerge in interactions between these two groups on social media. This study uses a pragmatic approach with a focus on the study of speech and speech acts, along with descriptive quantitative methods. The research data consists of written utterances obtained from social media posts and comment columns. The data are then classified based on the type of speech act (locutionary, illocutionary, and perlocutionary), and the type of illocutionary function (expressive, directive, assertive, and commissive). Furthermore, the data are analyzed quantitatively to determine the frequency and trends of each type of speech act. The results show that expressive and directive speech acts are the most dominant forms in interactions between the Sea-Blings and Knetz. These utterances are generally used to convey emotions, criticism, defense, and affirmation of group attitudes and identities. Differences in cultural background and perspective influence how speakers convey and interpret speech, potentially leading to misunderstandings and verbal conflict. This research is expected to provide insight into language usage patterns on social media and raise user awareness of the importance of using polite, wise, and contextually appropriate language in online communication.